Enhancement of waste heat recovery from exhaust stack silencers in A simple cycle gas turbine - Bouria Faqihi; Fadi Ghaith (International Journal of Thermofluids)
In this paper, a novel simple cycle gas turbine (GT) heat recovery system was modeled and evaluated through a computational method. Heat transfer channels were integrated into the existing nose and tail surfaces of the exhaust stack silencer baffles to avoid added turbine back-pressure, which is an issue with some of the existing waste heat recovery (WHR) models. The recovered heat was utilized for fuel gas heating, leading to energy savings and reduced CO2 emissions. Based on the conducted parametric studies, an enhanced heat transfer surface design was proposed with a combination of heat transfer from the nose and the modified tail that includes a wavy pattern.The description of the computational domain, mesh setup and mesh independence study were presented, and the heat transfer coefficient (HTC) was calculated. A comparison study was performed for the HTC values obtained by the computational model and the mathematical model [1] for the heat recovery from the silencers nose and tail. The results showed a variation of 16.8 % and 1.4 %, respectively. These values are within the typical accuracy range for common correlations of heat transfer in cross-flow. The net energy recovery ranged between 2.45 and 4.54 MW for different heat recovery combinations. The recovered heat that used in fuel gas heating resulted in fuel gas savings up to 68.97 kg/h and CO2 emissions reduction up to 1517 Tons/year.Further, the obtained results were qualitatively analyzed using flow visualization of the computational model. Based on the obtained findings, several options for further enhancement of heat recovery were proposed.